PEMANFAATAN DIGITAL MARKETING DALAM MENUNJANG BISNIS PENJUALAN SEPATU - Sofyan Mufti Prasetiyo; Rizky Aditya Suryo Leksono; Iqrom; Safarudin (CV. Multi Kreasi Media, 2023)
The Covid-19 pandemic has more or less affected the business world, especially for those selling shoes. This certainly forces these business actors to take full advantage of digital marketing. This is also in line with the increase of 16.5% of internet users in Indonesia from last year based on a survey from APJII. The purpose of this study is to find out how the implementation of digital marketing is carried out by business people selling shoes around Gunung Sindur and what are the obstacles faced when implementing digital marketing. This study in a structured qualitative using interviews, in depth interviews, and observation of entrepreneurs. The results of the study show that the use of digital marketing by business actors is carried out in different ways, namely Whatsapp and Facebook are used by Generation X for promotional purposes and for Generation Y using Tiktok, Shopee and Instagram by utilizing the live sale feature. The obstacles faced by each of these groups are different, but in general they are the same, namely towards their human resources. Generation X is constrained by knowledge of newer and broader platforms for sales. Meanwhile, the obstacle for Generation Y is the lack of experience in the business world so that they are very prone to becoming victims of online buying and selling fraud.